Living, Again: Population and Paradox in Recent Cinema. Issue 1 (July 2016) - Clavin, Keith
Abstract : The last several decades have witnessed a drastic increase in ecological writing, but also a substantial lack in regards to the discussion of human population control. This article argues that the deficiency has been reproduced within several recent examples of eco-cinema, Snowpiercer and Mad Max: Fury Road . Despite strong conservationist themes and narratives encouraging social revolution, the films encounter similar theoretical difficulties, and enact similar resulting absences, within their representational fields. As a consequence, the environmental topics are filtered through an anthropocentric lens that generates a set of paradoxes regarding human consumption, sacrifice and the visualisation of future sustainable states.